2019
DOI: 10.1155/2019/6431957
|View full text |Cite
|
Sign up to set email alerts
|

Post-TTM Rebound Pyrexia after Ischemia-Reperfusion Injury Results in Sterile Inflammation and Apoptosis in Cardiomyocytes

Abstract: Introduction Fever is frequently observed after acute ischemic events and is associated with poor outcome and higher mortality. Targeted temperature management (TTM) is recommended for neuroprotection in comatose cardiac arrest survivors, but pyrexia after rewarming is proven to be detrimental in clinical trials. However, the cellular mechanisms and kinetics of post-TTM rebound pyrexia remain to be elucidated. Therefore, we investigated the effects of cooling and post-TTM pyrexia on the inflammatory response a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 31 publications
(44 reference statements)
0
7
0
Order By: Relevance
“…In some patients with CAD, the rupture of atherosclerotic plaques in the coronary arteries due to fatigue, stress and other factors leads to the rapid accumulation of platelets, neutrophils and macrophages, which form emboli and block the vascular cavity, leading to the necrosis of cardiomyocytes. Myocardial cells are non-renewable, and thus myocardial blood perfusion must be restored as soon as possible ( 20 ). However, although the continuous development of PCI, CABG and other technologies has effectively improved myocardial blood perfusion, I/R injury is a major problem that remains to be addressed.…”
Section: Discussionmentioning
confidence: 99%
“…In some patients with CAD, the rupture of atherosclerotic plaques in the coronary arteries due to fatigue, stress and other factors leads to the rapid accumulation of platelets, neutrophils and macrophages, which form emboli and block the vascular cavity, leading to the necrosis of cardiomyocytes. Myocardial cells are non-renewable, and thus myocardial blood perfusion must be restored as soon as possible ( 20 ). However, although the continuous development of PCI, CABG and other technologies has effectively improved myocardial blood perfusion, I/R injury is a major problem that remains to be addressed.…”
Section: Discussionmentioning
confidence: 99%
“…[34] And in an in vitro study, the prevention of PRF obviously aggravated apoptosis of cells and release of in ammatory factors. [35] This study suggested that PRF was related to activation of in ammatory response and programmed cell death following the ischemia-reperfusion injury caused by CA. Since most works are focused on the clinical application of TTM, including optimal cooling temperature [5,36,37], practical methods of cooling for temperature control[6, 38, 39] and rate of rewarming following TTM [40,41], it is necessary to investigate the PRF with different body temperature and body temperature control in the future.…”
Section: Discussionmentioning
confidence: 90%
“…The previous study indicated that Rbm3 expression was reduced during fever/pyrexia, and reduced Rbm3 expression in turn led to elevated expression of Rbm3-targeted temperature-sensitive miRNAs (termed thermomiRs), such as miR-142-5p and miR-143 [83]. Moreover, cytoprotective Rbm3 expression was induced by cooling but suppressed by pyrexia in cardiomyocytes [84]. Together, these aforementioned ndings strongly suggests that Cirbp and Rbm3 might be implicated in hyperthermia for cancer therapy.…”
Section: Hyperthermia Signi Cantly Suppressed Cirbp Expression In Npc Cells and Xenograft Tumor Tissues Formed By Npc Cells In Nude Micementioning
confidence: 87%